Assistance in Preparing Anti-Anemia Food Menus to Prevent Stunting for Young Women and Posyandu Cadres in Tunjuk Village, Tabanan Regency Year 2023 - Ida Ayu Eka Padmiari; Pande Putu Sri Sugiani; I Wayan Ambartana (CV. AFDIFAL MAJU BERKAH, 2023)
Anemia is a health problem throughout the world, especially in developing countries, where an estimated 30% of the world's population suffers from anemia. Anemia in adolescent girls is still quite high. Anemia is a nutritional problem that often occurs in teenagers, especially young women. Anemia is a continuation of the impact of deficiencies in macronutrients (carbohydrates, proteins, fats) and micronutrients (vitamins, minerals). In adolescent girls, the need for iron increases because they experience regular menstruation which releases a certain amount of iron every month. This increase in the need for total blood volume is often not accompanied by adequate iron consumption, especially when teenage girls tend to want to have a slimmer body, so they often make various efforts, including going on a strict diet.Based on data from the 2022 Indonesian Nutrition Status Survey (SSGI), the prevalence of stunting among children under five in Tabanan Regency is still above the prevalence of stunting in Bali Province (8.0%) while in Tabanan Regency it is 8.2%. Research on female vocational school students in Tabanan Regency found that 54.2% had low levels of energy consumption, 32.5% had low levels of protein consumption, 88.0% had very low levels of iron consumption, 96.4% had very low levels of folic acid consumption. less and 78.3% have a very low level of vitamin B12 consumption and the level of knowledge about Anemia and CED, most of the Young Women have little knowledge about Anemia and CED, namely 84% less, 14% enough and 2% good. This lack of knowledge will affect the attitude of young women towards anemia and CED so that when they are pregnant they tend to experience anemia and CED and will give birth to stunted babies. The nutrition education that has been carried out is not enough to increase knowledge and especially attitudes of teenagers towards the risk factors for stunting, therefore the service will carry out training in preparing anti-anemia food menus for young women and Posyandu cadres in Tunjuk Village, Tabanan District. The priority solution is to improve the skills of young women and posyandu cadres to create anti-anemia food menus to prevent stunting by providing training. The method used to achieve this community service objective was to carry out training for 2 days for 50 young women and Posyandu cadres. This community service activity was carried out in Tunjuk Village, Tabanan District, Tabanan Regency in July 2023.